The Effect of Tax System Modernization on Taxpayer Compliance Based on Law in Indonesia - Kevin Putra Subagijo (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this study is to find out: The Impact of Modernization of the Tax Administration System, Tax Sanctions, and Individual Taxpayer Compliance. This study uses a quantitative approach and compares causes in different situations. 100 respondents were used in the incidental sampling technique of sampling. Questionnaires with closed questions were used to collect data. To obtain accurate results, the instrument was first tested for validity and reliability before distributing the questionnaires. In addition, the requirements of the regression test for hypothesis testing are used in conjunction with the traditional assumption test, namely the normality test, multicollinearity test, and heteroscedasticity test. Correlation coefficient test, coefficient of determination test, partial regression test, and simultaneous test are types of hypothesis testing used. According to the findings of the study, the modernization of the tax administration system benefits taxpayers significantly and positively. (2) Taxpayer compliance is not affected by tax sanctions. (3) Taxpayer compliance is positively and significantly influenced by taxpayer awareness. (4) Taxpayer compliance is positively and significantly influenced by the modernization of the tax administration system, tax sanctions, and awareness of the taxpayers collectively.